Some notes on countertransference from the perspective of relational psychoanalysis - Méndez, Matías (2023)
Psychoanalytically oriented psychotherapy has interpreted countertransference as an obstacle to the therapeutic process. Since Freud, the central tradition of psychoanalysis has insisted on the need to control and isolate the therapist’s subjectivity from the analytical field, promoting an attitude characterized by professional neutrality, anonymity, and abstinence. Relational psychoanalysis critiques this old idea, arguing that the subjective life of the psychotherapist, including his countertransference reactions, constitutes a fundamental ingredient of any treatment and that it cannot and should not be dissociated from the therapeutic encounter. This paper addresses some of the relational theorists’ main ideas about countertransference’s nature and function in psychoanalytic psychotherapy. This article reviews the main relational criticisms towards the ideal of analytic neutrality, describes the concept of “transference-countertransference matrix”, presents the development of the concept of “enactment” in relational clinical theory, and discusses some of the relational ideas about the use of therapist’s self-disclosure in psychoanalytic psychotherapy.